2000
DOI: 10.1021/jp002550p
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Chemical Study of Photoinjection Processes in Dye-Sensitized TiO2 Nanoparticles

Abstract: Results from quantum chemical INDO/S-CI calculations of the absorption properties of anatase TiO 2 nanoparticles sensitized by catechol and benzoic acid are reported. Experimental observations that catechol causes a strong shift in the TiO 2 absorption threshold, while benzoic acid does not, are explained from the calculations which indicate that only catechol introduces electronic levels in the TiO 2 band gap. The 420 nm excitation in the TiO 2 + catechol system responsible for the shift is seen to be a charg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
342
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 355 publications
(364 citation statements)
references
References 22 publications
20
342
2
Order By: Relevance
“…For the complexes, we used a stoichiometric cluster of anatase titania [(TiO 2 ) 38 ], exposing its (101) surface. This nanoparticle geometry has been used and reported in earlier works 11,12,19,21,22 where it was shown that the lowest excitation energy of the (TiO 2 ) 38 cluster is in agreement with the experimental bandgap. We performed geometry optimization of the isolated titania cluster within the two functionals and used its ground state structure to create dye- titania complexes.…”
Section: Calculation Detailssupporting
confidence: 73%
See 1 more Smart Citation
“…For the complexes, we used a stoichiometric cluster of anatase titania [(TiO 2 ) 38 ], exposing its (101) surface. This nanoparticle geometry has been used and reported in earlier works 11,12,19,21,22 where it was shown that the lowest excitation energy of the (TiO 2 ) 38 cluster is in agreement with the experimental bandgap. We performed geometry optimization of the isolated titania cluster within the two functionals and used its ground state structure to create dye- titania complexes.…”
Section: Calculation Detailssupporting
confidence: 73%
“…To this end, numerous dyes with different donors, linkers and acceptors have been synthesized and their performance as photo-sensitizers evaluated experimentally (see, for example, review articles by Mishra et al 9 and Hagfeldt et al 4 ). On the theoretical side, numerous studies [11][12][13][14][15][16][17][18][19][20][21][22][23] have been carried out to understand the photo-physics of dyes by themselves and in complexes with titania thin-films or nanoparticles. Most of these studies utilize time-dependent density functional theory (TD-DFT) to calculate UV/Vis spectra of the systems of interest.…”
mentioning
confidence: 99%
“…The next step in this work was to optimize the dye-titania structures. To do so, we prepared a neutral, stoichiometric cluster of (TiO 2 ) 38 exposing the anatase 101 surface, as described by Persson et al 41 . Previous studies 37,38,42 have shown that the lowest excitation energy of the (TiO 2 ) 38 cluster is in good agreement with the experimental bandgap of a nanoparticle of a few nanometer size.…”
Section: Computational Detailsmentioning
confidence: 99%
“…However, attempts to achieve further improvements in efficiency have been hindered by the lack of fundamental understanding of the molecular and electronic processes associated with the constituent operational steps. This problem continues to be a standing challenge, despite significant research effort reported in recent years, including experimental, 2-18 computational [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] and theoretical [37][38][39][40][41][42][43][44] studies. It is therefore essential to develop new experiments and theoretical studies to construct realistic models of dye-sensitized TiO 2 interfaces and gain insight on the design of surface-sensitization with optimum photon-to-current conversion efficiency.…”
Section: Introductionmentioning
confidence: 99%